Decision Support Systems in Supply Chain Management : A Cse Study of the Supply Chain At MAFC (Malaysian Agrifood Corporation Berhad) - Mukhammed, Abdussamat (2010)
This research project identified issues related to cold supply chain and implemented a case study research at a consolidated food supply chain company named Malaysian Agrifood Corporation Berhad, which produces fresh fruits and vegetebales. It endeavored to evaluate the practical application of Decision Support System (DSS) in managing the supply chain. Afterwards, based on the results this research provides possible recommendations on application.